Study on low temperature bonding solders for in-50 atomic % Sn/Cu joint for 3-D integrated circuit (IC) - Feng, Famin (2010)
In this project, the interaction between bi-layer eutectic In-Sn solder thin film and Cu for 3-D IC is studied. By using characterization methods such as scanning electron microscopy – energy dispersive x-ray spectroscopy (SEM-EDX) and shear test, the effects of bonding and annealing temperatures on the joint’s microstructure and shear strength can be determined. The results provide a good speculation to the intermetallic compound (IMC) formation at some of the samples that have undergone high annealing temperatures. A bonding mechanism is proposed based on the experimental results and elaborated as follows: 1. With the increase in bonding temperature, there is a significant increase in the true contact area between solder and copper with increasing temperature but remained relatively constant at higher bonding temperatures. There is no indication of increasing IMC formation with the increase in bonding temperature. 2. With the increase in the annealing temperatures, the contact area remained consistent while there is an indication showing good speculation of increased IMC formation. 3. There is a good indication showing a relationship between increasing shear strength with respect to the increase to the contact area and IMC.